2002
DOI: 10.1081/imm-120004800
|View full text |Cite
|
Sign up to set email alerts
|

Acute Psychological Stress Simultaneously Alters Hormone Levels, Recruitment of Lymphocyte Subsets, and Production of Reactive Oxygen Species

Abstract: Very little is known about the effects of acute psychological stress on the production of reactive oxygen species (ROS) by human phagocytic cells and the interplay between subjectively perceived stress, mediating hormones, variations in the number of peripheral leukocytes and ROS production. We measured psychological reactions, cardiovascular parameters, plasma catecholamines, plasma prolactin and cortisol as well as peripheral lymphocyte subsets in 13 experimental subjects undergoing a brief psychological str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…Previous studies have indicated an increase (Bagchi et al, 1999;Sivonova et al, 2004), decrease (Atanackovic et al, 2002;Yamaguchia et al, 2002) and no change (Huang et al, 2010) in indices of oxidative stress (i.e. plasma markers and ROS levels) in response to acute mental stress and during periods of lifestyle stress.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies have indicated an increase (Bagchi et al, 1999;Sivonova et al, 2004), decrease (Atanackovic et al, 2002;Yamaguchia et al, 2002) and no change (Huang et al, 2010) in indices of oxidative stress (i.e. plasma markers and ROS levels) in response to acute mental stress and during periods of lifestyle stress.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, stressful situations (i.e. exam periods (Sivonova et al, 2004) and public speaking (Yamaguchia et al, 2002)) and study model (human (Atanackovic et al, 2002) and animal (Bagchi et al, 1999) models) have varied significantly between studies, making it hard to draw valid and robust conclusions. To our knowledge, this was the first study utilising well standardized laboratory models of both acute inflammation and mental stress to test the sole influence of baseline inflammation on the oxidative stress responses to mental stress in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other studies have reported that stress increases the proportion of NK cells 21,22) . The decrease in NK cell counts after massage suggests that massage therapy may influence immune system, although it was not necessarily confirmed that massage activated immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Tools to test psychological stress are mainly questionnaires like the STAI and SDS, which rely on the subjective evaluations of subjects. In the search for objective assessment measures, the relationship between oxidative stress biomarkers and psychological stress has attracted attention in recent years [6] [7].…”
Section: Discussionmentioning
confidence: 99%